Determinan Nilai Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Hasbi Hasbi (Global Financial Accounting Journal, 2021)
Financial statements are the most important part of a company, this is because the financial statements are a means of communication that is the liaison between the parties involved in decision making related to the business continuity of the company. This study aims to examine the effect on investment decision, profitability and investment opportunity set on firm value. This study uses a sample of 10 banking company and is listed on the IDX during the 2015-2019 period. Data analysis techniques used in this study use multiple regression analysis. The results of this study indicate that the investment decision, profitability and investment opportunity set has not significant on firm value.